2015
DOI: 10.1039/c5tc01083g
|View full text |Cite
|
Sign up to set email alerts
|

Artificial opal photonic crystals and inverse opal structures – fundamentals and applications from optics to energy storage

Abstract: Photonic crystals (PhCs) influence the propagation of light by their periodic variation in dielectric contrast or refractive index. This review outlines the attractive optical qualities inherent to most PhCs namely the presence of full or partial photonic band gaps and the possibilities they present towards the inhibition of spontaneous emission and the localization of light. Colloidal self-assembly of polymer or silica spheres is one of the most favoured and low cost methods for the formation of PhCs as artif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
234
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 295 publications
(252 citation statements)
references
References 206 publications
(411 reference statements)
2
234
0
3
Order By: Relevance
“…Previous work has identified the influence of deposition time at a given voltage, for opal template formation. 32 Additional deposition approaches involving white noise during dip-coating methods, 13,32,33 spin-coating techniques 34 or other assembly approaches to minimize crack formation have been reasonably successful. 33,[35][36][37][38] We have found that an increase in voltage to 2.5 or 3.0 V does affect ordering on a SS substrate (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has identified the influence of deposition time at a given voltage, for opal template formation. 32 Additional deposition approaches involving white noise during dip-coating methods, 13,32,33 spin-coating techniques 34 or other assembly approaches to minimize crack formation have been reasonably successful. 33,[35][36][37][38] We have found that an increase in voltage to 2.5 or 3.0 V does affect ordering on a SS substrate (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation states determined from the V 2p and O 1s core-levels can be estimated according to 13.82 − 0.68 [O 1s − V 2p 3/2 ]. 60,61 The average vanadium oxidation state was calculated to be 4.912 for electrodeposited IO structure, and 5.116 (thus V 5+ ) for the non-templated planar V 2 O 5 film.…”
Section: D609mentioning
confidence: 99%
See 1 more Smart Citation
“…The (bio) sensors design and biological applications were another challenge using this type of materials. The inverse opal metamaterials are also used for the energy storage and communications, in solar cell technology, for electrochemical energy storage, at super capacitors, fuel cells, catalysts [1][2]. The applications are based of programmable properties of these 3D structured materials, which can be controlled by varying the physical and geometrical parameters of the samples and the applied fields.…”
Section: Inverse Opal Metamaterialsmentioning
confidence: 99%
“…Opal matrix nanocomposites on the base of colloidal crystal templates lled with various active components, providing an e ective interaction with electromagnetic eld, are very promising materials for applications in photonics, light beam-operating and energy storage systems [1,2]. Their properties are determined by both properties of the embedded components and composite topology.…”
Section: Introductionmentioning
confidence: 99%